IoT Based Wind/Solar Hybird Inverter - Ajeeth Kumar S.; Shabarish G.; Kishore Kannan A. (International Journal of Advances in Applied Sciences, 2016)
Paper deals with power control of a wind and solar hybrid generation system for connection operation with electric distribution system. Power control strategy is to extract the maximum energy available from varying condition of wind speed and solar irradiance while maintaining power quality at a safety level. In order to verify the maximum power variable speed control is come for wind turbine and maximum power is applied for PV system.  Inverter transfers the energy from the wind turbine and PV array into the grid by keeping common dc voltage constant. To ensure safety these inverters automatically shut down in the event of: High/Low AC-voltage; High/Low frequency; IOT is a key feature in which safety measurement is current and voltage.  The results show the control performance and  behavior of the wind/PV system .solar and wind are major possible ways were energy level are stored  in  battery, we implement to ensure that power transmission ways in hybrid pv/wind power are stored properly in batteries. Our aim is to monitor the current and voltage by means of IOT. The wave distribution of voltage and current is checked rapidly by using IOT. Non regular checking of voltage and current leads to total damage. And so we ensure that damage are monitored over IOT, variable power raise and drop are checked over by IOT. PV and wind  power.